PERIOPERATIVE COMPLICATIONS ASSOCIATED WITH ROUTINE PREOPERATIVE GLUCOCORTICOID USE AMONG PITUITARY SURGERY PATIENTS WITH NORMAL PREOPERATIVE HPA AXIS: A RETROSPECTIVE COHORT STUDY - Magnaye, Franz Michael; Paz-Pacheco, Elizabeth (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION This study determined the incidence of perioperative complications associated with routine preoperative glucocorticoid use in pituitary surgery patients with normal preoperative hypothalamo-pituitary-adrenal axis (HPA axis). METHODOLOGY In a retrospective chart review from 2011-2021, 243 patients with normal preoperative HPA axis who underwent pituitary surgery were divided into 2 groups: 1) with preoperative steroids and 2) without preoperative steroids, and evaluated for subsequent development of postoperative complications. RESULTS The incidence of composite postoperative complications of in-hospital mortality, postoperative infection, and postoperative diabetes insipidus was significantly increased among those with preoperative steroids compared to those without (58.33% versus 33.33%, p = 0.004), with an adjusted odds ratio of 2.90 (CI: 1.29 to 6.53, p = 0.010). Among the components of the composite outcome, post-operative diabetes insipidus was statistically higher among those given preoperative steroids (52.45% vs 28.21%, p = 0.006) with an adjusted OR of 3.31 (CI: 1.43 to 7.67, p = 0.005). The incidence of postoperative adrenal insufficiency was similar between the groups (20.15% with steroids vs 8.70% without steroids, p = 0.258). CONCLUSION Among patients with normal preoperative HPA axis who underwent pituitary surgery, routine preoperative steroid use was associated with an increased risk of composite postoperative complications (in-hospital mortality, postoperative infection, postoperative diabetes insipidus).